2022
DOI: 10.3390/cancers14051100
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Certain Terpenoids as Anticancer Agents: A Scoping Review

Abstract: Cancer is a life-threatening disease and is considered to be among the leading causes of death worldwide. Chemoresistance, severe toxicity, relapse and metastasis are the major obstacles in cancer therapy. Therefore, introducing new therapeutic agents for cancer remains a priority to increase the range of effective treatments. Terpenoids, a large group of secondary metabolites, are derived from plant sources and are composed of several isoprene units. The high diversity of terpenoids has drawn attention to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 245 publications
1
51
0
1
Order By: Relevance
“…These natural compounds or phytochemicals are largely categorized into alkaloids, terpenoids, and polyphenols, where the terpenoids and polyphenols are the major groups of plant's secondary metabolites, targeting several signaling pathways in the biological system (Zhu et al, 2018). The pharmacological properties of these compounds are due to their distinctive structures that enable them to interact with different key enzymes, receptors, antioxidant systems, and signaling cascades including transcription factors as well as cytokines (Safe et al, 2021;Santos et al, 2021;Kamran et al, 2022). For instance, the antioxidant activity of flavonoids, a subgroup of polyphenols, is correlated with the number of phenolic groups (Glevitzky et al, 2019), whereas anti-inflammatory and antidepressant effects are also associated with polyphenols (Hussain et al, 2016;Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These natural compounds or phytochemicals are largely categorized into alkaloids, terpenoids, and polyphenols, where the terpenoids and polyphenols are the major groups of plant's secondary metabolites, targeting several signaling pathways in the biological system (Zhu et al, 2018). The pharmacological properties of these compounds are due to their distinctive structures that enable them to interact with different key enzymes, receptors, antioxidant systems, and signaling cascades including transcription factors as well as cytokines (Safe et al, 2021;Santos et al, 2021;Kamran et al, 2022). For instance, the antioxidant activity of flavonoids, a subgroup of polyphenols, is correlated with the number of phenolic groups (Glevitzky et al, 2019), whereas anti-inflammatory and antidepressant effects are also associated with polyphenols (Hussain et al, 2016;Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, whatever natural products or chemical derivatives modulating angiogenesis share cardinal pathways that VEGF mediated, such as VEGFR2 pathway in vascular endothelial cells, HIF-1α/VEGF and its upstream transcriptional signaling in cancer cells, we concern and await the emergence of more potential targets for anti-angiogenesis therapy. Although other natural molecules in TCM also performed anti-angiogenesis property, comprising coumarins ( Wu et al, 2020 ), terpenoids ( Kamran et al, 2022 ), polysaccharides ( Li et al, 2021c ), and polyphenols ( Li et al, 2021c ; Marrero et al, 2022 ), they have no distinct difference in mechanisms in comparison with molecules we reported. Recently, angiopoietin (for instance, ang2) inhibition has been implied to be a strategy for overcoming the resistance of VEGF blockers in clinical, while the potential of natural molecules as angiopoietin inhibitors needs further observation ( Parmar and Apte, 2021 ).…”
Section: Perspectives and Conclusionmentioning
confidence: 57%
“…Many terpenoids exhibit various pharmacological properties, including anti- inflammatory, antitumoral, analgesic, antibacterial, antifungal, and antimalarial properties [ 241 , 242 , 243 ]. Moreover, various studies have also reported the antiviral potential of some of these compounds.…”
Section: Computer-based Investigations For Discovery Of Plant-derived...mentioning
confidence: 99%